Terminology and conceptual apparatus of tissue donation and tissue banking: interdisciplinary expert consensus (Part 2) - Irina A. Kirilova; Diana Ya. Aleynik; Igor V. Basankin; Svetlana A. Bozhkova; Natalya V. Borovkova; Aleksandr V. Burtsev; Sergey V. Vissarionov; Konstantin A. Vorobyev; Irina V. Gilevich; Svetlana A. Guzyukina; Olga V. Kozlovskikh; Ksenia V. Kulakova; et al. (Хирургия позвоночника, 2024)
The second part of an interdisciplinary expert consensus on tissue banking is presented. An analysis and attempt was made to systematize some of the terms and definitions used by tissue bank specialists in the process of their work and presented in the Federal laws and orders of the Ministry of Health of the Russian Federation regulating medical activities in the field of tissue donation and their clinical use.